An Irreducible Hip Dislocation with Femoral Head Fracture - Tae-Seong Kim; Chang-Wug Oh; Joon-Woo Kim; Kyeong-Hyeon Park (Journal of Trauma and Injury)
Urgent reduction is required in cases of traumatic hip dislocation to reduce the risk of avascular necrosis of the femoral head. However, in cases of femoral head fractures, the dislocated hip cannot be reduced easily, and in some cases, it can even be irreducible. This irreducibility may provoke further incidental iatrogenic fractures of the femoral neck. In an irreducible hip dislocation, without further attempting for closed reduction, an immediate open reduction is recommended. This can prevent iatrogenic femoral neck fracture or avascular necrosis of the femoral head, and save the natural hip joint.